2016
DOI: 10.1016/j.neuroimage.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in binding of the D2/3 receptor radioligand [11C](+)PHNO in healthy volunteers

Abstract: Objective Previous imaging studies with positron emission tomography (PET) have reliably demonstrated an age-associated decline in the dopamine system. Most of these studies have focused on the densities of dopamine receptor subtypes D2/3R (D2R family) in the striatum using antagonist radiotracers that are largely nonselective for D2R vs. D3R subtypes. Therefore, less is known about any possible age effects in D3-rich extrastriatal areas such as the substantia nigra/ventral tegmental area (SN/VTA) and hypothal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 68 publications
1
32
0
Order By: Relevance
“…It should be noted that the magnitude of increase found in the present study is consistent with the degree of decrease found in other studies using either [ 11 C]‐(+)‐PHNO (Di Ciano et al, ) or [ 11 C]‐raclopride (Martinez et al, ), suggesting that the changes observed in the present study were biologically relevant. In this regard, the basal level of BP ND observed in the DC, although small, is consistent with previous reports from a number of groups using [ 11 C]‐(+)‐PHNO (Di Ciano et al, ; Erritzoe et al, ; Matuskey et al, ; Matuskey et al, ; Matuskey et al, ; Searle et al, ). Thus, the increases observed in this study are not likely to be the result of an artefact due to low basal levels in the DC.…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that the magnitude of increase found in the present study is consistent with the degree of decrease found in other studies using either [ 11 C]‐(+)‐PHNO (Di Ciano et al, ) or [ 11 C]‐raclopride (Martinez et al, ), suggesting that the changes observed in the present study were biologically relevant. In this regard, the basal level of BP ND observed in the DC, although small, is consistent with previous reports from a number of groups using [ 11 C]‐(+)‐PHNO (Di Ciano et al, ; Erritzoe et al, ; Matuskey et al, ; Matuskey et al, ; Matuskey et al, ; Searle et al, ). Thus, the increases observed in this study are not likely to be the result of an artefact due to low basal levels in the DC.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, this work demonstrated that OB individuals exhibited higher D 2/3 Rs in both extrastriatal (ie, SN/VTA and pallidum) and striatal (ie, VST) regions associated with reward and motivation with the latter finding being the first published difference in any addiction-like condition with [ 11 C](+)PHNO in the striatum. These results were unaffected by adjustment for potential confounding factors such as age (Ishibashi et al, 2009;Kim et al, 2011;Matuskey et al, 2016;Nakajima et al, 2015;Volkow et al, 2000) or tracer injection parameters, and were confirmed with a whole-brain voxel-wise analysis. Moreover, after adding a cohort of OW individuals, we observed a positive linear association between BMI and D 2/3 R availability in the aforementioned regions that also persisted after adjusting for age, gender, and tracer injection parameters.…”
Section: Discussionmentioning
confidence: 61%
“…As part of the secondary analyses, 14 otherwise healthy OW (BMI 25-29.9 kg/m 2 ) individuals were added to the analysis to examine the linear association between BMI and D 2/3 R availability in a large, broad-BMI-ranged cohort (see Tables 1 and 2 for means and standard deviations of demographics, injection parameters, and radioactivity data for all individuals studied). All participants with the exception of one D 2/3 R alterations in obesity EC Gaiser et al OW participant were non-nicotine/tobacco users and some have been reported on elsewhere (Matuskey et al, 2015;Matuskey et al, 2016). Once research participants were eligible for the study, they were asked to abstain from all food and liquids (except for water) the night prior to presenting to the Yale PET Center for imaging until the scanning procedures were completed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the high affinity radiotracer [18F]fallypride, we extended these findings, showing that there is also significant loss of presynaptic DRD2 in the midbrain, which may reflect either age-related decline in the number of dopamine neurons (as previously observed in postmortem human brains (Fearnley and Lees, 1991)) and/or the expression of autoreceptors on those neurons. PET studies using the DRD3-preferential tracer [11C]-(+)-PHNO have not observed age-dependent decline in midbrain BP ND (Matuskey et al, 2016; Nakajima et al, 2015), potentially suggesting that the age-related [18F]fallypride BP ND decline at least partially reflects autoreceptor loss with age rather than neuronal loss, which would have presumably been similarly detected by [11C]-(+)-PHNO.…”
Section: Discussionmentioning
confidence: 99%